(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In Delhi Schools, whereby the use of CLT as a means of instruction for demonstrating English is fairly new, the current research looks at the challenges faced in implementing Communicative Language Teaching (CLT). The article commences with a succinct historical account of Communicative Language Teaching (CLT), subsequently expounding upon its defining attributes and purposes. Subsequently, the present study examines the functions of educators and students, in addition to instructional practices, within the framework of “Communicative Language Teaching” (CLT). Subsequently, the text explores the obstacles that impede the implementation of “Communicative Language Teaching” (CLT) in certain nations across the globe, as well as the efforts to introduce CLT. The preceding research indicates that the implementation of CLT in Delhi is hindered by significant obstacles, including but not limited to Large class numbers, educational and evaluation inconsistencies, cultural insensitivity, insufficient preparation, and unfavourable socioeconomic background. The researchers’ recommendations for addressing the aforementioned challenges are illuminated by the aforementioned text. Ultimately, the paper culminates by presenting implications for future research endeavors aimed at investigating the methods of implementing “Communicative Language Teaching” (CLT) in the context of expansive classrooms situated in Delhi.